The effectiveness of pure Stichopus horrens extract toothpaste in reducing plaque-induced gingivitis following orthodontic bonding : A triple-blinded randomized controlled trial - Abu Bakar, Noraini; Jayah, Nurul Idayu; Mohamed, Nurul Rafhana; Mohamed Ali, Suhaila; Nasir, Siti Hajjar; Hashim, Ridzwan; Kharuddin, Azrul Fazwan (2020)
Introduction: Gingivitis is one of the commonest problems faced by patients with fixed appliances (FA) as there is close relation between the appliances to gingival sulcus. Stichopus horrens (SH) is a sea cu- cumber from the Indo-Pacific that has medical healing properties which have been traditionally used. Objective: To assess the effects of toothpaste containing aqueous SH extract on plaque-induced gingivitis following orthodontic bond-up and to identify the optimal concentration of SH. Methods: A single-centred; triple-blinded randomized controlled trial conducted in 40 patients with FA. Participants were randomly assigned to one of the four groups with toothpaste which has concentration of SH extract of 0%, 3%, 6% or 9%. The statistician, the participants and the researchers involved in data collection were kept blinded from the allocation. Gingival Index (GI) and Bleeding on Probing (BOP) for each group were taken at day 0,7,14 and 30. Results: 9% of SH-containing toothpaste (SHCT) showed most substantial result as there were significance difference of GI (P 1⁄4 0.020) from Day 7 to 14 and from Day 0 to 14 (P 1⁄4 0.020). There was also significance difference of BOP from Day 0 to 14 (P 1⁄4 0.022) and from Day 0 to 30 (P 1⁄4 0.027). Significant difference was seen in 3% of SHCT group with the decrease of GI (P 1⁄4 0.004) from Day 1 to 14. There were no significant difference noted for 0% and 6% SHCT. Conclusion: The 9% SHCT is the most effective concentration to reduce both the gingival inflammation (up to day 14) and bleeding on probing (up to day 30).